2020
DOI: 10.4085/1062-6050-0372.19
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Biochemical Changes After Gait Biofeedback in Individuals With Anterior Cruciate Ligament Reconstruction

Abstract: Context Gait biomechanics are linked to biochemical changes that contribute to the development of posttraumatic knee osteoarthritis in individuals with anterior cruciate ligament reconstruction (ACLR). It remains unknown if modifying peak loading during gait using real-time biofeedback will result in acute biochemical changes related to cartilage metabolism. Objective To determine if acutely manipulating peak vertical ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…These findings are not surprising because previous work has demonstrated that the uninjured limb may develop altered gait patterns that are similar to the ACLR limb (11). These data suggest that multiple loading parameters (daily steps and biomechanics) are simultaneously affected in some individuals after ACL injury and ACLR (2,15,16). Our study indicates that future efforts should be made to measure both gait biomechanics and loading frequency after ACLR to best understand the cumulative loading changes in specific patients.…”
Section: Discussionmentioning
confidence: 94%
“…These findings are not surprising because previous work has demonstrated that the uninjured limb may develop altered gait patterns that are similar to the ACLR limb (11). These data suggest that multiple loading parameters (daily steps and biomechanics) are simultaneously affected in some individuals after ACL injury and ACLR (2,15,16). Our study indicates that future efforts should be made to measure both gait biomechanics and loading frequency after ACLR to best understand the cumulative loading changes in specific patients.…”
Section: Discussionmentioning
confidence: 94%
“…Most articles excluded at this stage included inappropriate outcome measures. 11 studies were judged to satisfy inclusion criteria and were included for analysis and synthesis [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. References of these articles were reviewed to identify any further relevant studies.…”
Section: Resultsmentioning
confidence: 99%
“…Low . biomechanical gait patterns more similar to uninjured controls and decreases serum biomarker concentrations of cartilage turnover (22,35,36). In contrast, individuals with ACLR-T1ρ Low profiles who decrease KAM between 6 and 12 months post-ACLR start with higher KAM values than the uninjured controls, and the trend to decrease KAM between 6 and 12 months post-ACLR in the ACLR-T1ρ Low group may be an attempt to express loading profiles similar to uninjured controls.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, we speculate that individuals with the most deleterious changes in cartilage composition who demonstrate lower KAM profiles than uninjured controls 6 months after ACLR may benefit from interventions seeking to increase KAM magnitudes to values that match uninjured controls. A single session of gait retraining in individuals with an ACLR that cues an increase in peak vertical ground reaction force results in biomechanical gait patterns more similar to uninjured controls and decreases serum biomarker concentrations of cartilage turnover (22,35,36). In contrast, individuals with ACLR-T1ρ Low profiles who decrease KAM between 6 and 12 months post-ACLR start with higher KAM values than the uninjured controls, and the trend to decrease KAM between 6 and 12 months post-ACLR in the ACLR-T1ρ Low group may be an attempt to express loading profiles similar to uninjured controls.…”
Section: Discussionmentioning
confidence: 99%